Bodotria jejuensis sp. nov. (Crustacea, Cumacea, Bodotriidae), a new Korean cumacean - Lee, Chang-Mok; Kim, Sung-Hyun; Kim, Young-Hyo (Zootaxa, 2016)
A new species of Cumacea belonging to the genus Bodotria Goodsir, 1843 was collected from the Jeju-do Island, Korea. The new speices, Bodotria jejuensis sp. nov. is similar to B. similis Calman, 1907, B. rugosa Gamô, 1963, B. carinata Gamô, 1964, and B. biplicata Gamô, 1964 in having a pitted carapace, prominent dorso-lateral carina, and unarticulated endopod of uropod. However, longish elliptical shape of carapace, well-developed dorso-lateral carina and distinct lateral ridge are the major characteristics which serve to distinguish the new species from its congeners. The new species is fully illustrated and extensively compared with related species. A key to the Korean Bodotria species is also provided.